Pengenalan Kain Ulos di Daerah Kabupaten Toba Samosir Menggunakan Realitas Tertambah Berbasis Android - Hara Goliat; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
The purpose of this study is to provide information in the form of an introduction to the general public, especially people in Medan who have a scope of students or young people today, with a very attractive appearance and design in the form of 3d and the application can be used without having to turn on internet (offline ). Ulos fabric AR application can be used for learning media and introduction to tourists looks rather interesting. The method in developing this application uses Multimedia Development Life Cycle (MDLC) and Unified Modeling Language (UML) to create an application model design. Research using these methods will produce an Android-based AR recognition application. The development of this application was designed using the C # programming language and based on Vuforia data.